Your very own robot - Montgomery, R. A.; Newton, Keith (Waitsfield, Vt. Chooseco, 2007)
Your parents are scientists. One day, they throw out some pieces of a robot in the trash. If you can figure out how to put the pieces together, you'll have a robot of your very own!
"A Dragonlark book."
Revised version of 1982 publication published by Bantam.
"There are 12 possible endings" --Cover.
90697
Keywords: Plot-your-own stories; Robots; Adventure